Guidelines to build the bridge between sustainability and integrated management systems: A way to increase stakeholder engagement toward sustainable development. (20th May 2022) - Vieira Nunhes, Thaís; Espuny, Maximilian; Lauá Reis Campos, Thalita; Santos, Gilberto; Bernardo, Merce; Oliveira, Otávio José
Abstract: The balanced development and management of sustainability demands the alignment of Corporate Sustainability (CS) strategy with management systems so that sustainability can be effectively inserted into all organizational levels and thus promote stakeholder engagement. Therefore, to support the development of CS, the structure, processes, indicators, and instructions of Integrated Management System (IMS) can be used. This study aims to propose guidelines for the alignment of CS and IMS, based on the cross analysis of seven case studies. This objective was achieved through the identification of elements that can positively or negatively impact the alignment of CS with the IMS, which served as the basis for proposing the guidelines to build a bridge for CS development from the IMS. This work brought as a scientific contribution the upgrade of the block of knowledge on the contributions between IMS and CS, bringing some validation of knowledge from scientific articles in the real context of industrial companies, and additions and refinements to the state of the art on the subject. In addition, the applied contribution of the results stands out, which will provide managers with a framework to intervene in organizations with structural modifications that will make them greener, socially appropriate and more profitable, thus promoting the achievement of the global goals of sustainable development proposed in Agenda 2030.